Rivaroxaban in antiphospholipid syndrome (RAPS) protocol: a prospective, randomized controlled phase II/III clinical trial of rivaroxaban versus warfarin in patients with thrombotic antiphospholipid syndrome, with or without SLE. (September 2015) - Cohen, H; Doré, C J; Clawson, S; Hunt, B J; Isenberg, D; Khamashta, M; Muirhead, N
Introduction: The current mainstay of the treatment of thrombotic antiphospholipid syndrome (APS) is long-term anticoagulation with vitamin K antagonists (VKAs) such as warfarin. Non-VKA oral anticoagulants (NOACs), which include rivaroxaban, have been shown to be effective and safe compared with warfarin for the treatment of venous thromboembolism (VTE) in major phase III prospective, randomized controlled trials (RCTs), but the results may not be directly generalizable to patients with APS. Aims: The primary aim is to demonstrate, in patients with APS and previous VTE, with or without systemic lupus erythematosus (SLE), that the intensity of anticoagulation achieved with rivaroxaban is not inferior to that of warfarin. Secondary aims are to compare rates of recurrent thrombosis, bleeding and the quality of life in patients on rivaroxaban with those on warfarin. Methods: Rivaroxaban in antiphospholipid syndrome (RAPS) is a phase II/III prospective non-inferiority RCT in which eligible patients with APS, with or without SLE, who are on warfarin, target international normalized ratio (INR) 2.5 for previous VTE, will be randomized either to continue warfarin (standard of care) or to switch to rivaroxaban. Intensity of anticoagulation will be assessed using thrombin generation (TG) testing, with the primary outcome the percentage change in endogenous thrombin potential (ETP) from randomization to day 42. Other TG parameters, markers of in vivo coagulation activation, prothrombin fragment 1.2, thrombin antithrombin complex and D-dimer, will also be assessed. Discussion: If RAPS demonstrates i) that the anticoagulant effect of rivaroxaban is not inferior to that of warfarin and ii) the absence of any adverse effects that cause concern with regard to the use of rivaroxaban, this would provide sufficient supporting evidence to make rivaroxaban a standard of care for the treatment of APS patients with previous VTE, requiring a target INR of 2.5.